Corn Chopping Machine Innovation as an Efficient Animal Feed Solution for Corn Farmer Groups in Kading Village, Tanete Riaja District, Barru Regency - Zulkifli Djafar; Wahyu H. Piarah; Zuryati Djafar; Taufiqqurrahman Zulkifli; Fithriyah Arief Wangsa (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2026)
The availability of animal feed is a crucial factor in increasing livestock productivity, but the process of shredding corn, the main ingredient in feed, is still largely done manually by farmers in Kading Village, Tanete Riaja District, Barru Regency. This community service activity aims to improve feed processing efficiency through the application of appropriate technology in the form of a corn shredding machine. The activity involved 20 participants from local farmer and livestock groups and was carried out over four months through the stages of needs survey, machine design and construction, socialization, operational training, and field assistance. Evaluation was conducted using pre-test and post-test instruments with 10 assessment parameters. The results showed a significant increase from the average pre-test score of 47.6% to 74.3%, or an increase of 56%, reflecting the effectiveness of the training. In addition, the efficiency of shredding time increased by 60%, and the shredded size was more uniform, thus improving feed quality. This activity made a significant contribution to improving the knowledge, technical skills, and productivity of farmer groups, as well as strengthening the use of appropriate technology in providing animal feed in Kading Village.